CircRnas in atherosclerosis, with special emphasis on the spongy effect of circRnas on miRnas. Issue 5 (4th March 2023) - Cheng, Chenglong; Wang, Yuting; Xue, Qiuyun; Huang, Yurong; Wang, Xiao; Liao, Faxue; Miao, Chenggui
ABSTRACT: Atherosclerosis (AS) is a chronic inflammatory disease, which leads to atherosclerotic rupture, lumen stenosis and thrombosis, and often endangers life. Circular RNAs (circRNAs) are a special class of non-coding RNA molecules, whose abnormal expression has been proved to be closely related to human diseases, including AS. Both the abnormal regulation of circRNAs and the sponging effect on miRNAs would lead to changes in gene expression in the form of epigenetic modification, ultimately leading to the formation of AS. CircRNAs can be used as peripheral blood markers of AS, and play an important regulatory role in the proliferation, migration, inflammation and apoptosis of vascular smooth muscle cells, endothelial cells and macrophage, which are key cells for the development of AS. The in-depth understanding of circRNAs in AS not only provides a new method for the diagnosis of AS, but also provides a new idea for the treatment of AS.